Studi Komparasi Strategi True or False dengan Strategi Crossword Puzzle terhadap Hasil Belajar PKn SiswaKelas III SD Muhammadiyah PK PracimantoroTahun Ajaran 2015/2016 - Yayang, Monica; , Dra. Risminawati, M.Pd (2016)
Background problem in this research is the teacher has not been able to implement appropriate strategies in learning of Civic Education. Though many active learning strategies that can be used as a true or false strategy and crossword puzzle strategy. This research aims to determine: (1) differences in learning outcomes of Civic Education the use of true or false strategy and crossword puzzle strategy, (2) a larger strategy influence between true or false strategy with crossword puzzle strategy to learning outcomes of Civic Education. This research is quantitative experiments with research subjects are students of 3th grade A and 3th grade B SD Muhammadiyah PK Pracimantoro academic year 2015/2016. Data collection techniques using tests and documentation. Test instruments used validity and reliability. Data were analyzed using t-test, preceded by test for normality and homogeneity. Based on data analysis with α=5% results obtained tcount > ttabel, namely 2,530> 1,998 with the average value learning outcomes of Civic Education 3th grade A is greater than 3th grade B namely 83.788> 76.87. The conclusion this research are: (1) there are differences in learning outcomes of Civic Education in the use of true or false strategy and crossword puzzle strategy on a 3th grade students of SD Muhammadiyah PK Pracimantoro academic year 2015/2016, (2) true or false strategy greater influence than crossword puzzle strategy to the learning outcomes of Civic Education at 3th grade students of SD Muhammadiyah PK Pracimantoro academic year 2015/2016.